Rewilding the small stuff: the effect of ecological restoration on prokaryotic communities of peatland soils. Issue 10 (17th August 2020) - Andras, Jason P; Rodriguez-Reillo, William G; Truchon, Alexander; Blanchard, Jeffery L; Pierce, Erin A; Ballantine, Katherine A
ABSTRACT: To investigate the effect that restoration has on the microbiome of wetland soils, we used 16S amplicon sequencing to characterize the soil prokaryotic communities of retired cranberry farms that were restored to approximate the peat wetlands they once were. For comparison, we also surveyed the soil communities of active cranberry farms, retired cranberry farms and natural peat wetlands that were never farmed. Our results show that the prokaryotic communities of active cranberry farms are distinct from those of natural peat wetlands. Moreover, 4 years after restoration, the prokaryotic community structure of restored cranberry farms had shifted, resulting in a community more similar to natural peat wetlands than to active farms. Meanwhile, the prokaryotic communities of retired cranberry farms remained similar to those of active farms. The observed differences in community structure across site types corresponded with significant differences in inferred capacity for denitrification, methanotrophy and methanogenesis, and community composition was also correlated with previously published patterns of denitrification and carbon sequestration measured from the same soil samples. Taken together, these results suggest that ecological restoration efforts have the potential to restore ecosystem functions of soils and that they do so by 'rewilding' the communities of resident soil microbes. Abstract : This aerial photograph of the Mass Audubon Tidmarsh Wildlife Sanctuary shows the bog surface 4 years after ecological restoration from over a century of cranberry agriculture.